2017
DOI: 10.1063/1.4982720
|View full text |Cite
|
Sign up to set email alerts
|

A critical comparison of Lagrangian methods for coherent structure detection

Abstract: We review and test twelve different approaches to the detection of finite-time coherent material structures in two-dimensional, temporally aperiodic flows. We consider both mathematical methods and diagnostic scalar fields, comparing their performance on three benchmark examples: the quasiperiodically forced Bickley jet, a two-dimensional turbulence simulation, and an observational wind velocity field from Jupiter's atmosphere. A close inspection of the results reveals that the various methods often produce ve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
239
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(243 citation statements)
references
References 88 publications
4
239
0
Order By: Relevance
“…Analytical methods define eddies as coherent structures by mathematical estimations of coherence. Some of these studies include Lagrangian coherent structures identified by material rotation relative to the mean rotation of the deforming fluid volume (Haller et al, 2016;Tarshish et al, 2018), the change in location of a fluid particle induced by infinitesimal changes in its initial position (finite-time Lyapunov exponent; Beron-Vera et al, 2008;Hadjighasem et al, 2017), and geometrical analysis using transfer operators and invariant manifolds (Froyland & Padberg, 2009;Froyland et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Analytical methods define eddies as coherent structures by mathematical estimations of coherence. Some of these studies include Lagrangian coherent structures identified by material rotation relative to the mean rotation of the deforming fluid volume (Haller et al, 2016;Tarshish et al, 2018), the change in location of a fluid particle induced by infinitesimal changes in its initial position (finite-time Lyapunov exponent; Beron-Vera et al, 2008;Hadjighasem et al, 2017), and geometrical analysis using transfer operators and invariant manifolds (Froyland & Padberg, 2009;Froyland et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…4 are the computed diagnostic fields obtained from the flow from time 1 to 0, and the right panel shows extracted LCSs based on some simple choices of procedures P. We do not use the most sophisticated methods available for such extraction, because (i) we are only interested in a qualitative comparison, and (ii) more refined extraction methods will result in approximately the same entities. We moreover emphasize that our intention is not to compare or critically evaluate different LCS methods (readers are referred to papers such as [110,143] for this), but rather to illustrate that results arising from different LCS methods are not necessarily the same, and do not necessarily have a connection to GLCS sets chosen according to some specification.…”
Section: Passive Scalar Advectionmentioning
confidence: 99%
“…Such methods include the bottom-up approach proposed by Kuhn et al, 19 the top-down approach proposed by Guan et al, 20 and a method based on attribute-field proposed by Zhang et al 18 The Lagrangian specification is also used to discover Lagrangian coherent structures (LCS) in flows. 21 For these studies, vortices can be identified using the finite-time Lyapunov exponent (FTLE). 41 Furthermore, methods that group trajectories using network theory 42 or trajectory analysis 43 for spatial segmentation have been proposed.…”
Section: Related Workmentioning
confidence: 99%
“…For every pair of observation points (α, α ) that satisfy |α α | ≤ ε, the distance between the limiting distributions correspond to these points is calculated with Eq. (21). Consequently, the elements of the similarity matrix can be calculated from the distance as shown in Eq.…”
Section: B Clustering Based On Similaritymentioning
confidence: 99%
See 1 more Smart Citation